급성심근경색증 환자의 증상 인지와 건강행위 이행이 내원시간에 미치는 영향 - 한은주(Han, Eun Ju); 김정선(Kim, Jeong Sun) (Sŏngin Kanho Hakhoe chi, 2015)
Purpose: This study was to investigate the relationship among the symptom recognition, health behavior compliance, and the hospital arrival time to identify factors influencing the hospital arrival time in patient with acute myocardial infarction (AMI). Methods: The subjects of this study were 200 patients with AMI in C hospital in D city. Data were analyzed using descriptive statistics, independent t-test, One way ANOVA, Pearson's correlation coefficients, and stepwise multiple liner regression tests. Results: Level of symptom recognition and health behavior compliance was low. The median value of hospital arrival time was 4.48 hours (ST-segment Elevation Ml was 2.43 hours and Non ST-segment Elevation MI was 7.83 hours). Among the studied factors, only symptom recognition had a statistically significant positive correlation with health behavior compliance (r=0.38, p<.001). Factors influencing the hospital arrival time were MI classification, diabetes mellitus (DM) and transport vehicle to the 1st hospital, and they accounted for 13% of the variance for hospital arrival time in AMI patients. Conclusion: To prevent the delay of hospital arrival time in MI patients, a more robust nursing strategic intervention according to MI classification and DM is necessary; further education on the importance of transportation utilization is also mandated.